Ubezpieczenie dla literaturoznawstwa.Uwagi na marginesach Poetyki - Gleń, Adrian (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The text is an attempt to indicate innovatory terminological solutions and their critical reception of the so-called cultural theory of literature, being formed in the last decade, on the basis of the last proposal included in Poetyka doświadczenia (“Poetics of Experience”) by Ryszard Nycz. The author of the essay concentrates on the fundamental humanistic notions, for example experiencing, happening, paradigmaticality, interdisciplinarity in the studies into literature or intertextuality, which, from this viewpoint, are subject to redefinition and a kind of conceptualization. A separate place in these considerations is occupied by the comparison of the stance of the author of Sylwy współczesne with the recent writings of Michał Paweł Markowski and the argument with the analysis of specific case studies included in the ending of Poetics of Experience.